2015
DOI: 10.1016/s0924-9338(15)30428-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione as an Antioxidant Defense System in Schizophrenia and Bipolar 1 Disorder

Abstract: Introduction: There is strong evidence that oxygen free radicals may play an important role in the pathophysiology of major mental illnesses such as schizophrenia and bipolar disorders. Aim of the study: To detect the difference in the level of total glutathione mainly in serum sample of schizophrenic patients compared to bipolar patients and healthy control. Subject and methods: A case-control cross sectional study, the sample included thirty schizophrenic patients, 30 patients with bipolar I disorder (manic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent past reports reveals that blockade of serotonin receptors by LH improves the dose dependent negative symptoms (somnolence, akathisia, nausea and parkinsonism)of psychoses and other side effects can be minimized by cutting off the higher dose to lower, which can easily be achieved by enhancing the bioavailability (Citrome, 2011;Madan, Pawar, & Dua, 2015;Meyer et al, 2009 (ROS) (Dean et al, 2009;Wang, Shao, Sun, & Young, 2009). The depletion in Glutathione (GSH) levels is also an major factor which contribute in the pathophysiology of psychosis and bipolar disorder (Andreazza, Wang, Salmasi, Shao, & Young, 2013;Fathy, Bayoumy, Abdel Mawla, Aladrousy, & Alhanafy, 2015;Gawryluk, Wang, Andreazza, Shao, & Young, 2011;Nucifora et al, 2017).…”
Section: Dysregulation Of 5-ht Is Associated With Diarrhoea or Constimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent past reports reveals that blockade of serotonin receptors by LH improves the dose dependent negative symptoms (somnolence, akathisia, nausea and parkinsonism)of psychoses and other side effects can be minimized by cutting off the higher dose to lower, which can easily be achieved by enhancing the bioavailability (Citrome, 2011;Madan, Pawar, & Dua, 2015;Meyer et al, 2009 (ROS) (Dean et al, 2009;Wang, Shao, Sun, & Young, 2009). The depletion in Glutathione (GSH) levels is also an major factor which contribute in the pathophysiology of psychosis and bipolar disorder (Andreazza, Wang, Salmasi, Shao, & Young, 2013;Fathy, Bayoumy, Abdel Mawla, Aladrousy, & Alhanafy, 2015;Gawryluk, Wang, Andreazza, Shao, & Young, 2011;Nucifora et al, 2017).…”
Section: Dysregulation Of 5-ht Is Associated With Diarrhoea or Constimentioning
confidence: 99%
“…Moreover, schizophrenia and bipolar disorder are associated with increase in the cellular oxidative stress through generation of reactive oxygen species (ROS) (Dean et al, 2009; Wang, Shao, Sun, & Young, 2009). The depletion in Glutathione (GSH) levels is also an major factor which contribute in the pathophysiology of psychosis and bipolar disorder (Andreazza, Wang, Salmasi, Shao, & Young, 2013; Fathy, Bayoumy, Abdel Mawla, Aladrousy, & Alhanafy, 2015; Gawryluk, Wang, Andreazza, Shao, & Young, 2011; Nucifora et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Abnormal levels of intracellular GSH are associated with many diseases, such as cancer, Parkinson's disease, Alzheimer's disease, schizophrenia and so on. [3][4][5][6][7] Recent reports have shown that the concentration of GSH can reach 10 mM in cancer cells, which is much higher than that in most normal cells (more than fivefold). 8,9 This fact provides an opportunity to distinguish cancer cells from normal cells and develop GSH-guided photodynamic therapy strategies.…”
Section: Introductionmentioning
confidence: 99%